2019
DOI: 10.1038/s41598-019-55378-2
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Interferon Regulatory Factor 1 Causes Susceptibility to Colitis-Associated Colorectal Cancer

Abstract: The mechanisms linking chronic inflammation of the gut (IBD) and increased colorectal cancer susceptibility are poorly understood. IBD risk is influenced by genetic factors, including the IBD5 locus (human 5q31), that harbors the IRF1 gene. A cause-to-effect relationship between chronic inflammation and colorectal cancer, and a possible role of IRF1 were studied in Irf1-/- mice in a model of colitis-associated colorectal cancer (CA-CRC) induced by azoxymethane and dextran sulfate. Loss of Irf1 causes hyper-sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…It was previously reported that IRF1 is a transcriptional regulator that is central in activating macrophages by proinflammatory signals such as the interferon- γ (IFN- γ )-mediated signaling pathway ( 65, 99 ). Loss of irf family members IRF1 or IRF8 causes severe susceptibility to infections in mammals ( 100, 101 ). Consistent with these studies, it is not surprising that irf1 is highly expressed in M1 phenotype macrophages (inflammatory) (Figure 2E).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that IRF1 is a transcriptional regulator that is central in activating macrophages by proinflammatory signals such as the interferon- γ (IFN- γ )-mediated signaling pathway ( 65, 99 ). Loss of irf family members IRF1 or IRF8 causes severe susceptibility to infections in mammals ( 100, 101 ). Consistent with these studies, it is not surprising that irf1 is highly expressed in M1 phenotype macrophages (inflammatory) (Figure 2E).…”
Section: Discussionmentioning
confidence: 99%
“…5b). MCP1, which we termed the UC program, was enriched for genes located in genetic risk loci for IBD and UC 16 (P = 4.15*10 −4 ; Online Methods), particularly in its up-regulated set, including CCL20 47 (TA1 and TA2), PRKCB (CD8 and macrophages), and IRF1 48 (macrophages and CD4). Most of the UC program genes, including 19 from risk loci (Supplementary Table 2), are cell-type specific in the program, although they are expressed in various cell types.…”
Section: Ulcerative Colitis Mcp Marks Genetic Risk Loci and Prognosismentioning
confidence: 99%
“…The family of IRFs includes nine members: IRF1, IRF2, IRF3, IRF4/PIP/LSIRF/ICSAT, IRF5, IRF6, IRF7, IRF8/ICSBP, and IRF9/ISGF3γ, that participate in the regulation of both development and activation of the immune system cells [90]. Notably, IRF1, IRF5, and IRF8 contribute to pro-inflammatory polarization of macrophages while IRF3 and IRF4 regulate M2 polarization macrophages [24,25,31,33]. Thus, IRF1 is involved in M1 polarization in human macrophage cell line U937 in response to IFNγ and LPS by upregulation of IL-12, IL-6, IL-23 and CD86 and downregulation of M2-specific marker CD206 [24].…”
Section: Interferon Regulatory Factorsmentioning
confidence: 99%
“…Notably, IRF1, IRF5, and IRF8 contribute to pro-inflammatory polarization of macrophages while IRF3 and IRF4 regulate M2 polarization macrophages [24,25,31,33]. Thus, IRF1 is involved in M1 polarization in human macrophage cell line U937 in response to IFNγ and LPS by upregulation of IL-12, IL-6, IL-23 and CD86 and downregulation of M2-specific marker CD206 [24]. The knockdown of IRF1 in macrophages induces their pro-tumor activity regarding to hepatocellular carcinoma cell lines HepG2 and SMMC-7721, promoting proliferation and invasion of tumor cells [24].…”
Section: Interferon Regulatory Factorsmentioning
confidence: 99%